The effectiveness of brief personalized normative feedback in reducing alcohol-related problems amongst University students: protocol for a randomized controlled trial - Foxcroft David R; Moreira Teresa (BMC, 2008)
Abstract Background Studies have shown that university/college students tend to have an exaggerated view of the quantities of alcohol being consumed by their peers. Making students aware of this misperception may help change behaviour and reduce problem drinking. Methods/Design A Solomon Three Group Design will be used. There is one intervention group and two control groups, controlling separately for measurement and for intervention effects. Recruitment, consent, randomisation and data collection are all on-line. The primary outcomes are AUDIT Score, weekly consumption, perceived social norms, and alcohol related problems; secondary outcomes include alcohol expectancies and other health behaviours. Discussion This trial will provide information on the effectiveness of an on-line personalized normative feedback intervention for alcohol misuse in university students. Trial registration International Standard Randomised Controlled Trial Number: ISRCTN30784467